Problem-Based Learning in Indonesian Language Instruction Using Children’s Storybooks as a Means to Improve Learning Outcomes in Indonesian - Lia Widiastuti; Ni Kadek Dwi Pramita; Luh Gede Fera Yulia Dewi; Ni Wayan Anik Purnama Dewi; I Nyoman Sudiana; Ida Bagus Putra Yasa (International Journal of Language and Literature, 2025)
Currently, Indonesian language lessons are often less popular with students because they are considered monotonous and not contextual. In addition, many students still experience difficulties with understanding reading material, summarizing story content, and developing critical thinking skills in Indonesian language learning. Therefore, this study aims to describe the effectiveness of Problem-Based Learning (PBL)-based Indonesian language learning assisted by children's storybooks in improving the learning outcomes of sixth-grade elementary school students. This study employed a one-shot case study design with 30 sixth-grade students as participants. The research instrument was a multiple-choice objective test consisting of 25 questions that experts had validated. The test data were analyzed using SPSS version 25 to obtain a quantitative picture of student learning outcomes. The results showed that the average student learning outcome was 79.67, with the majority of students in the high and very high categories, and no students in the low category. These findings indicate that the PBL learning model, supported by children's storybooks, can significantly improve learning outcomes. Thus, PBL-based Indonesian language learning assisted by children's storybooks is recommended as an alternative learning strategy that is innovative, contextual, and effective at the elementary school level.